Failed Dermal Allograft Procedures for Irreparable Rotator Cuff Tears Can Still Improve Pain and Function: The "Biologic Tuberoplasty Effect". Issue 8 (19th August 2019) - Mirzayan, Raffy; Stone, Michael A.; Batech, Michael; Acevedo, Daniel C.; Singh, Anshuman
Background: Acellular dermal matrices (ADMs) have been used in the treatment of shoulders with massive rotator cuff tears (MRCTs). Despite clinical improvement, correlation of clinical findings with ADM integrity on imaging has not been investigated. Hypothesis: The pain in shoulders with MRCTs is partially due to bone-to-bone contact between the tuberosity and acromion. Coverage of the tuberosity with an intact graft or a graft that is torn in a way that the tuberosity remains covered will act as an interpositional tissue, preventing bone-to-bone contact and leading to clinical improvement. Study Design: Case series; Level of evidence, 4. Methods: Between 2006 and 2016, a total of 25 shoulders with MRCTs underwent a procedure with an ADM. Pre- and postoperative visual analog scale (VAS) results, American Shoulder and Elbow Surgeons (ASES) score, Hamada grade, and Goutallier classification were reviewed. A postoperative magnetic resonance imaging (MRI) was obtained in 22 (88%) shoulders. The status of the graft was divided into the following categories: type I, intact graft; type II, graft tear with tuberosity covered; and type III, graft tear with tuberosity uncovered (bare). Results: The mean patient age was 61 years (range, 49-73 years), and the mean follow-up was 25.6 months (range, 10-80 months). Mean length from surgery to postoperative MRI was 13.9 months (range, 6-80 months). The graft was torn in 59% (13/22 shoulders). Significant improvements were found in VAS and ASES scores (7 vs 0.7 and 32.6 vs 91.2, respectively; P < .01) for type I grafts and in VAS and ASES scores (8.1 vs 1.3 and 26.3 vs 84.6, respectively; P < .01) for type II grafts. No difference was found in postoperative VAS and ASES (0.7 vs 1.3 and 91.2 vs 84.6, respectively; P = .8) between type I and type II grafts. No improvement was seen in VAS (7.3 vs 5.7; P = .2) or ASES (30.6 vs 37.2; P = .5) for type III grafts. Conclusion: MRI appearance of the graft has a significant impact on functional outcomes. Patients with an intact graft or a graft tear leaving the tuberosity covered have lower pain and higher functional scores than those in whom the torn graft leaves the tuberosity uncovered.